Psychogenic Erectile Dysfunction: A Multidisciplinary Problem - A. O. Vasiliev; N. V. Astakhov; P. A. Arutyunyan; O. R. Aliev; L. A. Khodyreva; D. Yu. Pushkar (Здоровье мегаполиса)
Erectile dysfunction is a multifactorial problem that requires various treatment approaches based on the factors affecting disease development. Erectile dysfunction is one of the most serious clinical and social issues among men. It’s obvious that a full sexual life is one of the most important components of physical and mental health. Recent sociological data show that sexual health is the key not only to a good quality of life, but also to a longer life expectancy. It is noted that combining the traditional three-stage therapy – oral drugs, penile injection therapy and penile implantation – with ongoing psychotherapy can significantly improve the treatment results. Accordingly, it becomes important and crucial for a specialist to be aware of the timely referral of a patient to a psychotherapist.